Local System and Spatial Change – The Case of Bóly in South Transdanubia - Maurel, Marie-Claude; Póla, Péter (Discussion Papers, 2012)
Along with the political, economic and social transition, spatial differentiation processes that are spreading out in Central Europe raise the issue of spatial change’s own timetable. Urban polarization process, reactivation of the East-West asymmetry, industrial restructuring and economic depression of rural peripheries, are all parts of a new spatial differentiation process. Since the begin¬ning of the 1990s, rural areas have experienced massive scale transformation What are the forces at play in the differentiation process and what are the territorial reshaping patterns? Our research project intends to look at the ongoing spatial reorganization in rural areas in three Central European coun¬tries, Hungary, Czech Republic and Poland. Empirical data which had been regularly collected from fieldwork are used to assess social and economic changes and to analyse how the spatial forms that shape rural areas are being reworked. These changes occurred in two main steps: dis¬mantling of state and collective structures, and diversification of economic func¬tions and social uses of rural areas. By observing the Post-Socialist transfor¬mation at the local level, the study intends to establish a comprehensive under¬standing of the territorial trajectories. The example of the changes that have affected the local system in Bóly reveals the importance of the relations between social stakeholders in institutional ar¬rangements both political and economic. Although the path taken appears to de¬pend on the manner in which the stakeholders emerged from collectivisation, it belongs even more to the long history of settlement and improvement of this ter¬ritory by the Swabian rural communities. A long process of accumulation of know-how has produced a set of specific resources.